Experimental identification and analysis of macronuclear non-coding RNAs from the ciliate Tetrahymena thermophila - Andersen, Kasper L. (Oxford University Press, 2012)
The ciliate Tetrahymena thermophila is an important eukaryotic model organism that has been used in pioneering studies of general phenomena, such as ribozymes, telomeres, chromatin structure and genome reorganization. Recent work has shown that Tetrahymena has many classes of small RNA molecules expressed during vegetative growth or sexual reorganization. In order to get an overview of medium-sized (40–500 nt) RNAs expressed from the Tetrahymena genome, we created a size-fractionated cDNA library from macronuclear RNA and analyzed 80 RNAs, most of which were previously unknown. The most abundant class was small nucleolar RNAs (snoRNAs), many of which are formed by an unusual maturation pathway. The modifications guided by the snoRNAs were analyzed bioinformatically and experimentally and many Tetrahymena-specific modifications were found, including several in an essential, but not conserved domain of ribosomal RNA. Of particular interest, we detected two methylations in the 5′-end of U6 small nuclear RNA (snRNA) that has an unusual structure in Tetrahymena. Further, we found a candidate for the first U8 outside metazoans, and an unusual U14 candidate. In addition, a number of candidates for new non-coding RNAs were characterized by expression analysis at different growth conditions.